Penerapan model pembelajaran STAD dan TGT terhadap hasil belajar penjasorkes materi senam lantai roll belakang - Fajar Dwi Fadillah; Donny Anhar; Ibnu Fatkhu Royana (YLPK Mahardhika, 2021)
The background of this research is the ability of learning outcomes in the psychomotor, cognitive and affective aspects of both the XI IPS 1 grade students who are still many who are below KM. The learning method that will be used by researchers in conducting research is the learning model using the STAD and TGT models. The results showed: (1) there was an effect of the learning model on learning outcomes in class XI IPS 1 (STAD) as evidenced by the results of the paired simple t test with a significant value of Sig. (2-tailed) 0.039> 0.05 and the average post-test graph value of learning outcomes. (2) there is an effect of the learning model on learning outcomes in class XI IPA 1 (TGT) as evidenced by the results of the paired simple t test with a significant value of Sig. (2-tailed) 0.039> 0.05 and the average post-test graph value of learning outcomes. The conclusions of this study indicate that the results of the study of the STAD or TGT learning model applied to class XI IPS 1 and class XI IPA 1.Even by simple paired simple t test class XI IPS 1 Significance level: ? = 5% = 0, 05 Testing Criteria: If Sig. (2-tailed)> ? then H0 is accepted. For Class XI IPA 1 TGT Significance Level: ? = 5% = 0.05 Testing Criteria: If Sig. (2-tailed)> ? then H0 is accepted.